2010
DOI: 10.1073/pnas.1008117107
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of human mesenchymal stromal cells (MSCs) into 3D spheroids enhances their antiinflammatory properties

Abstract: Previous reports suggested that culture as 3D aggregates or as spheroids can increase the therapeutic potential of the adult stem/progenitor cells referred to as mesenchymal stem cells or multipotent mesenchymal stromal cells (MSCs). Here we used a hanging drop protocol to prepare human MSCs (hMSCs) as spheroids that maximally expressed TNFα stimulated gene/protein 6 (TSG-6), the antiinflammatory protein that was expressed at high levels by hMSCs trapped in the lung after i.v. infusion and that largely explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

82
942
3
11

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 832 publications
(1,038 citation statements)
references
References 36 publications
82
942
3
11
Order By: Relevance
“…On comparing monolayer cultured MSCs with 3D multicellular spheroids, it was shown that the 3D environment altered cell size, expression levels of cell surface antigens, and the osteogenic differentiation potential, 10 and enhanced the suppression of inflammatory responses. 11 Cells grown in 3D cultures showed reduced proliferation rate, altered their adhesion structures, and changed the transcription levels of distinct adhesion molecules. 12 In addition, a 3D environment can affect in vitro cell mechanobiology and extracellular matrix proteins, for example, collagens and fibrins.…”
Section: Introductionmentioning
confidence: 99%
“…On comparing monolayer cultured MSCs with 3D multicellular spheroids, it was shown that the 3D environment altered cell size, expression levels of cell surface antigens, and the osteogenic differentiation potential, 10 and enhanced the suppression of inflammatory responses. 11 Cells grown in 3D cultures showed reduced proliferation rate, altered their adhesion structures, and changed the transcription levels of distinct adhesion molecules. 12 In addition, a 3D environment can affect in vitro cell mechanobiology and extracellular matrix proteins, for example, collagens and fibrins.…”
Section: Introductionmentioning
confidence: 99%
“…Bone differentiation potential of MSCs maintained in medium supplemented with rice bran extract Several studies have reported that three-dimensional spheroids of MSCs have enhanced biological functions, including the ability for osteogenic or adipogenic differentiation, or anti-inflammatory properties (Wang et al 2009;Miyagawa et al 2011;Bartosh et al 2010). Therefore, we hypothesized that the aggregation of rMSCs in STK1 with RBE would increase their potential for osteogenic differentiation.…”
Section: Treatment Of Mscs With Rice Bran Extract: Inducing Aggregatimentioning
confidence: 99%
“…Recent studies reported that MSCs readily aggregate and formed spheroids by culturing in particular substrates, such as micro-patterned substrates (Wang et al 2009), hydrophobic nano-pillars (Brammer et al 2011) and chitosan membranes (Hsu et al 2012), or by specialized methods, such as the hanging drop method (Bartosh et al 2010). Additionally, a recent study reported that N-cadherin is involved in the aggregation of MSCs (Hsu et al 2012), implying that RBE might induce aggregation of MSCs through expression of N-cadherin.…”
Section: Treatment Of Mscs With Rice Bran Extract: Inducing Aggregatimentioning
confidence: 99%
“…현재 개발 된 많은 3차원 배양 방법 중 배아줄기세포의 응집 (aggregation)의 유도로 embryonic body를 형성시키는 방법이 중간엽 줄기세포 배양에도 적용되어 구형의 sphere를 형성시키는 3 차원 배양 방법이 개발되었다 [4]. 세포의 aggregation을 유도 하여 3차원 배양하면 세포 사이의 신호 전달이 활발하게 이 루어지며 2차원 배양 방법보다 생체 내 환경을 더 유사하게 재현할 수 있기 때문에 세포의 치료적 잠재성을 높일 수 있다 [5]. 3차원 배양 방법과 함께 세포치료제 분야에서 줄기세포를 이용함에 있어 세포의 증식과 특성을 증대시키기 위해 공배 양 (co-culture) 방법이 적용되었다.…”
Section: Introductionunclassified